2004
DOI: 10.1289/ehp.6579
|View full text |Cite
|
Sign up to set email alerts
|

Sample characterization of automobile and forklift diesel exhaust particles and comparative pulmonary toxicity in mice.

Abstract: Two samples of diesel exhaust particles (DEPs) predominate in health effects research: an automobile-derived DEP (A-DEP) sample and the National Institute of Standards Technology standard reference material (SRM 2975) generated from a forklift engine. A-DEPs have been tested extensively for their effects on pulmonary inflammation and exacerbation of allergic asthmalike responses. In contrast, SRM 2975 has been tested thoroughly for its genotoxicity. In the present study, we combined physical and chemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
96
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 35 publications
9
96
1
3
Order By: Relevance
“…This indicated that, across chemical classes, A-EOM contained more S9-dependent mutagenicity than did the SRM 2975 EOM. Consistent with this is the evidence presented here and by Singh et al (2004) for greater amounts of PAH-type mutagenicity and PAHs in the A-DEPs compared with SRM 2975. There is ample evidence that the genotoxic activity associated with the EOM of DEPs inhaled into the lung may be bioavailable by virtue of the solubilization and dispersion properties of pulmonary surfactant components (Belisario et al 1984;Keane et al 1991;King et al 1981).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This indicated that, across chemical classes, A-EOM contained more S9-dependent mutagenicity than did the SRM 2975 EOM. Consistent with this is the evidence presented here and by Singh et al (2004) for greater amounts of PAH-type mutagenicity and PAHs in the A-DEPs compared with SRM 2975. There is ample evidence that the genotoxic activity associated with the EOM of DEPs inhaled into the lung may be bioavailable by virtue of the solubilization and dispersion properties of pulmonary surfactant components (Belisario et al 1984;Keane et al 1991;King et al 1981).…”
Section: Discussionsupporting
confidence: 90%
“…The lack of mutagenic activity in the hexane fraction (Tables 7 and 8) was consistent with the presence of unsubstituted alkanes and alkenes, which are not mutagenic. These results are also supported by the photomicrographs and other chemical and combustion data demonstrating that much of the A-EOM is uncombusted fuel, possibly neutral alkanes and alkenes (Singh et al 2004), which would have eluted in the hexane fraction.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations